Report and recommendations on NEDA and regional development - CPA Study Team (Philippine Journal of Public Administration, 1989)
An examination of the functions and organization of the National Economic and Development Authority (NEDA) in relation to regional development planning and administration brings out the following observations: top-down approach in regional planning; weaker emphasis on regional development as gleaned from NEDA's structure for planning; and less attention to interregional planning and coordination. Thus, it is recommended that the planning and implementation process be strengthened through decentralization of operations and responsibilities to NEDA's lower level organizations and to local governments. It is also proposed that planning's importance as guide for development, and NEDA's role in development planning and its implementation be further reinforced.